Altered expression of transcription factors IRF4 and IRF8 in peripheral blood B cells is associated with clinical severity and circulating plasma cells frequency in patients with myasthenia gravis. (3rd April 2018) - Zhang, Yong; Jia, Xiao; Xia, Yan; Li, Hao; Chen, Fei; Zhu, Jie; Zhang, Xiuying; Zhang, Yanyan; Wang, YuZhong; Xu, Yanan; Pan, Meng; Huang, Xiaoyu; et al.
Abstract: Previous studies have shown that interferon regulatory factor-4 (IRF4) and IRF8 play critical but distinct roles in the differentiation of B cells into plasma cells (PCs). In the present study, we aimed to measure the expression levels of IRF4 and IRF8 in B cells from patients with myasthenia gravis (MG) and to investigate whether the expression of IRF4 and IRF8 associates with pathogenesis of MG. A total of 35 anti-acetylcholine receptor (AChR) antibody (Ab)-positive patients with MG [20 generalized MG (GMG) and 15 ocular MG (OMG) and 25 healthy donors were recruited in this study. The quantitative myasthenia gravis score (QMGS) was used to evaluate the clinical severity. Real-time PCR and Western blot were used to measure the levels of IRF4 and IRF8 expressed in peripheral blood B cells. Peripheral blood CD138 + PCs were assayed by flow cytometry. Our data demonstrated that the mRNA/protein levels of IRF4 and IRF8 were significantly higher and lower, respectively, in patients with OMG/GMG groups compared with healthy controls. In addition, IRF4 expression was significantly higher and IRF8 expression was significantly lower in GMG group than in OMG group. Pearson's correlation analysis revealed that IRF8 expression was negatively correlated with clinical severity, PCs frequency and anti-AChR Ab levels, while IRF4 expression and IRF4/IRF8 ratio was positively correlated with these parameters in two MG subgroups. Finally, glucocorticoid treatment can relieve the imbalance of IRF4/IRF8 in peripheral blood B cells, and this restoration is accompanied by reduced PCs frequency and clinical symptoms. These evidences suggest that IRF4 and IRF8 are important in the counter-balancing mechanisms controlling differentiation of PCs in MG. The disruption of the balanced IRF4/IFR8 ratio in B cells may play important roles in the pathogenesis of MG and offer a promising therapeutic target for the development of novel immunotherapy for MG patients.